No Differences in Outcomes Scores or Survivorship of Unicompartmental Knee Arthroplasty Between Patients Younger or Older than 55 Years of Age at Minimum 10-Year Followup. Issue 6 (June 2019) - Lee, Merrill; Chen, Jerry; Shi Lu, Chia; Lo, Ngai Nung; Yeo, Seng Jin
Abstract: Background: Although patients who have undergone unicompartmental knee arthroplasty (UKA) report improvements in functional outcomes, orthopaedic surgeons tend to avoid UKA in younger patients due to implant survivorship concerns. As a result, few studies specifically have examined the outcomes of patients 55 years and younger. Questions/purposes: Is there a difference between two cohorts of patients: those 55 years and younger and those 56 years and older who underwent UKA in terms of: (1) functional outcomes scores, (2) quality-of-life scores, and (3) implant survivorship free from all-cause revision. Methods: Between 2004 and 2007, 100 patients 55 years and younger underwent UKA at one institution. Of those, three (3%) died, and 13 (13%) were lost to followup before the 10-year minimum required for this study, leaving 84 patients available for propensity score matching. During that same period, 343 patients older than 56 years underwent UKA; 48 (14%) died, and 59 (17%) were lost to followup before 10 years, leaving 236 patients available in that group for potential inclusion. After propensity score matching to account for confounding preoperative variables (surgeon, patient's body mass index, and sex), the patients were divided into two groups based on age: (1) 55 years and younger, (2) 56 years and older. There were 71 patients in each group, with minimum followup of 10 years. The mean age in the group of patients 55 years and younger was 52 years (range, 45–55 years) and that of the older patients was 64 years (range, 56–80 years). The mean (range) followup in both groups was 13 years (range, 11–15 years). Patient functional outcomes, quality of life scores, and implant survivorship were assessed for both groups of patients. To detect a minimum clinically important difference of 5 points in the Oxford Knee Score (OKS), a sample size of at least 68 patients in each group would be required to achieve a power of 0.95. Results: With the numbers available, there were no differences between patients 55 years and younger and those 56 years and older in terms of OKS (18 ± 6 versus 20 ± 8, mean difference -1.8; 95% CI, -4.1 to 0.5; p = 0.133) and Knee Society Knee Score (84 ± 16 versus 79 ± 21, mean difference 4.7; 95% CI, -1.8 to 11.2; p = 0.157) at 10 years postoperatively. With the numbers available, there were no differences between patients 55 years and younger and those 56 years and older in terms of the physical component summary (PCS) (47 ± 10 versus 48 ± 11, mean difference -0.4; 95% CI, -4.0 to 3.2; p = 0.827) and the mental component summary (MCS) (52 ± 12 versus 51 ± 12, mean difference 1.4; 95% CI, -2.6 to 5.4; p = 0.491) of the SF-36 at 10 years postoperatively. Finally, we found no differences with the numbers available between patients 55 years and younger and those 56 years and older in terms of survivorship free from all-cause revision at a minimum of 10 years followup (both groups had the same 10-year revision-free rate of 0.96; 95% CI, 0.91–1.00). Conclusions: Because we found few differences between patients 55 years and younger and those older than that in terms of functional outcomes, quality of life, and implant survivorship after UKA, we believe that appropriately selected younger patients should not be excluded from the potential benefits of undergoing UKA, especially in the hands of high-volume surgeons. Level of Evidence: Level III, therapeutic study.